(3ZQQ GdaQGFO hOQQ GdbdGFOs - (3YHjO Gddg Hf eMeO GdgGTej GdMSjfj GdaQZGfj HQgGf GdOjf, GdeYQha HGdYHQj , hjfYJ HGdTQja GdeQJVj,J (B743 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf JChjd BjI bGd Gddg JYGdi hjSCdhec Yf GdQhM bd GdQhM ef GeQ QHj s
(3BNQgG (B:s
(3hgPG HNdGa eG Ydjg GcKQ GdfGS ef eQGYGI CeQ GdMGVQ GdbQjH hGgd Mb GdHYjO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B136s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1201s
Keywords: (3GdfMhs